A bibliometric analysis of global research status and trends in irritable bowel syndrome and gut microbiota metabolites - Shi-Ran Wang; Shi-Ran Wang; Jie Zhou; Jia-Yi Zhang; Shi-Fang Li; Guo-Jie Hu (Frontiers in Microbiology)
BackgroundMetabolites derived from the gut microbiota are substantial contributors to the pathophysiology of Irritable Bowel Syndrome (IBS). As our understanding of the mechanisms underlying gut microbiota metabolites advances, significant progress has been made in research exploring the correlation between gut microbiota metabolites and IBS. Nevertheless, a comprehensive synthesis of research foci and trends in this domain is still lacking. Consequently, integrating scientometric methods with a range of analytical tools can facilitate the identification of key research areas and potential future study directions.MethodsThe present study employed scientometric tools, including VOSviewer, Bibliometrix software, CiteSpace, Tableau, and R software, to collect and analyze research literature on IBS and gut microbiota metabolites. This comprised an analysis of journal publications and their impact, the identification of prolific authors, the establishment of national research collaboration networks, and the co-occurrence analysis of keywords.ResultsThe analysis revealed that, following screening, a total of 1,489 documents were obtained, with a gradual increase in the number of publications starting from 2006. The United States, China, and the United Kingdom have been identified as the primary hubs of this research field. The leading research institutions were identified as University College Cork, the Mayo Clinic, and the University of California. In the domain of research under discussion, John F. Cryan, Timothy G. Dinan, and Gerard Clarke are the most prominent authors. Multiple analyses of the keywords revealed that research on gut microbiota metabolites in irritable bowel syndrome primarily focuses on the functions and mechanisms of action of specific metabolites (1). Emerging research hotspots on gut microbial metabolites influencing IBS are centered on bile acids. In contrast, chain fatty acids have been the most studied metabolites in past research. (2) Gut microbiota metabolites primarily affect IBS through the critical role of the gut-brain axis and are closely associated with anxiety-like behaviors. (3) Experimental types related to gut microbiota metabolites and IBS research.ConclusionThis study employed bibliometric analysis to map the knowledge structure and identify research hotspots in gut microbiota metabolites and IBS, providing insights for future studies.